How significant are fiscal interactions in federations? A meta-regression analysis - Joan Costa-i-Font; Filipe De-Albuquerque; Hristos Doucouliagos (Center for Economic Studies and ifo Institute (CESifo), 2011)
A large literature examines government fiscal interactions in federations. However, the empirical evidence is scattered and inconclusive, especially with respect to the size of interactions, as well as the institutional and economic determinants underpinning them. This paper uses meta-regression analysis to quantify the size of these inter-jurisdictional fiscal interactions and to explain the heterogeneity in empirical estimates. First, we find significantly stronger interactions among municipalities and nations than among intermediate levels of government. Second, tax interactions are, in general, stronger than expenditure interactions, and horizontal tax interactions appear to be stronger than vertical interactions. Third, both tax competition and yardstick competition are supported by the data, though the former appears to produce stronger interactions. Fourth, capital controls, voter turnout and the design of decentralization all shape fiscal interactions; political competition and fiscal decentralization both increase horizontal tax competition and they decrease vertical tax competition. Finally, much of the variation between estimates can be explained by country heterogeneity, differences in econometric specification and estimation strategies.
Keywords: H50; H73; R10; 330; fiscal interactions; meta-regression; intergovernmental competition; yardstick competition; Finanzpolitik; Finanzföderalismus; Steuerwettbewerb; Yardstick Competition; Public Choice; Meta-Analyse; Schätzung; Welt